2017
DOI: 10.4238/gmr16039758
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genome similarities using the non-decimated wavelet transform

Abstract: The wavelets have become increasingly popular in the field of bioinformatics due to their capacity in multiresolution analysis and space-frequency localization; the latter particularity is acquired due to a moving window that runs through the analyzed space. As a feature, they have a better ability to capture hidden components of biological data and an efficient link between biological systems and the mathematical objects used to describe them. The decomposition of signals/sequences at different levels of reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…The Aggregated Absolute Value method presented the most similar pattern of the formation of groups to the aggregated variance method; however the formation of their larger group with similar sequences, as represented in the Figure 2b, does not match with the results obtained in the previous studies 8,9 .…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The Aggregated Absolute Value method presented the most similar pattern of the formation of groups to the aggregated variance method; however the formation of their larger group with similar sequences, as represented in the Figure 2b, does not match with the results obtained in the previous studies 8,9 .…”
Section: Discussionmentioning
confidence: 53%
“…We studied the Daubechies wavelet with 4 null moments and 5 levels of details, and the coefficients of each level are represented by (d1, d2, d3, d4, d5), where d1 corresponds to the level with less details and d5 to the level with more details 8 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first group with DS and DR sequences (lower energy) and the second group with MDR and XDR sequences (highest energy). Ferreira et al (2017) showed that the behavior of GC-content sequence can be succinctly described regarding the non-decimated wavelet transform, and indicated how this characterization can be used to improve clustering of the similar strains of the genome of the Mycobacterium tuberculosis, having a very efficient level of detail. The clustering analysis using the energy obtained at each level of the analyzed sequences was essential to verify the dissimilarity of the sequences.…”
Section: Introductionmentioning
confidence: 99%